Awareness and attitude about mental illness in the rural population of India: A mixed method study - Kaustubh S. Kulkarni; Mudita N. Joshi; Harshal S. Sathe; Chetna Maliye (Indian Journal of Psychiatry)
Context: Recent systematic review and meta-analysis of public attitudes have shown that despite improvements in mental health literacy, public attitudes and desire for social distance with mental illnesses have remained stable over time. Aims: To assess the awareness and attitude of the rural community towards mental disorders using the CAMI scale. Materials and Methods: This mixed method study was conducted under the ICMR-STS grant scheme after IEC approval. It included administration of a pre-tested questionnaire adapted from CAMI scale on 196 adults aged 18-60 years from an adopted village in the field practice area of medical college along with 8 in-depth interviews of key people in the same community. Thematic analysis was done for the qualitative part whereas for the quantitative part, Pearson’s correlation coefficient, independent t-test, ANOVA and Kruskall-wallis test were used. Results: Age was positively correlated with the attitude of authoritarianism, social restrictiveness, CMHI and showed a negative correlation with attitude of benevolence. Females showed higher scores for authoritarianism and social restrictiveness. There was a statistically significant difference between APL and BPL groups for authoritarianism attitude towards the mentally ill (P value = 0.02) and CMHI (P value = 0.033). It was observed that with increase in the education levels there was a rise in the mean score of the values for the attitude of benevolence but the difference wasn’t statistically significant (P > 0.05). Thematic analysis of the key informant interviews suggested various perceptions of the community regarding mental illness, available options for management, current practices of the community and what can be done further to improve facilities for mental health. Conclusions: People in the community have a varied perspective to mental illnesses which has changed for the better over time but community still approaches quacks first which warrants the need for more awareness. For this, feasibility and effectiveness of increasing involvement of females from the community in health-related decisions can be explored further. We recommend further awareness generation in the younger generation with community-based research on perceptions of the community about mental health. This will provide more practical and feasible solutions to complement the national mental health program.